PERFORMANCE AND HEMATOLOGICAL PARAMETERS OF LOMAN BROWN HEN AS INFLUENCED BY Balsomina mamodica SUBSTITUTING LASOTA VACCINE IN SEMI-ARID ZONE OF NIGERIA (FUDMA JOURNAL OF SCIENCES, 2022)
The study was carried out at University Research Farm of the Department of Animal Science, Kano University of Science and Technology, Wudil, to evaluate the growth performance and hematological parameters of Loman Brown hen as influenced by inclusion levels of Balsomina mamodica substituting lasota vaccine in semi-arid zone of Nigeria. The birds were randomly allotted into four treatment in a completely randomized design with fifty (50) birds per treatment. Treatment 1 was given lasota vaccine (NCDV) at first, third, seven and seventeen weeks respectively. Treatment 2 was given Garafuni 0.5g per litre for six days in the week whereas Treatment 3, 1.0g per litre and Treatment 4, 1.5g per litre of Garafuni for four and two days in the week respectively. At the end of the study, blood samples were collected from five (5) birds from each treatment for hematological studies. The result shows that, intake and performance of Lohman Brown Hen administered Balsomina mamordica substituting Lasota vaccine at laying phase is shown in Table 1. The result indicated that no significant (P>0.05) difference was shown with respect to initial body weight (IBWT), final body weight (FBWT), weight gain (WT), average weight gain (AWG), feed conversion ratio (FCR) and metabolic mass.T4 recorded the highest mean value (600.0) whereas animals in T2 (0.5g garahuni) had the least mean value (525.00). Data on haematological parameters of Loman brown hen are presented on Table 2. The result showed non- significant differences among the treatments means. Haemogloblins, packed cell. Highest mean
Keywords: Growth performance, heamatological parameters, Loman brown, Lasota vaccine